DYNAMICS OF SHARIA IMPLEMENTATION IN ENGLAND - Dinil Abrar Sulthani; Mukhlishin Mukhlishin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Sharia is part of Islamic teachings or law. Sharia is implemented by every Muslim wherever he is, especially in England. The purpose of this thought paper is to describe the assumptions of British citizens and the Government towards sharia, discuss the conditions and factors of implementing sharia, and discuss the impact of sharia reform in England. This thought paper uses a qualitative research method with a literature study approach. This paper comes from an in-depth analysis of the data, documents, books, journals, and reports on sharia in the UK. The data is processed by analysis and interpretation to present a complete understanding of the study of sharia implementation. The results of this study of thought show that, slowly and gradually, the residents and the British Government recognize and respect the existence of sharia in England as a religion practiced by Muslims. Factors influencing implementation include the different distribution of the Muslim population in each region of England, immigrant Muslims still adhering to the original religious teachings of their country of origin, and the establishment of sharia institutions or boards to support the implementation of sharia in England.